Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.4102/sajpsychiatry.v13i2.30
|View full text |Cite
|
Sign up to set email alerts
|

Longer duration of breastfeeding associated with risk of developing schizophrenia

Abstract: <p><strong>Background.</strong> Some studies have suggested that breastfeeding may be protective against the development of schizophrenia. Such a theory supports the neurodevelopmental hypothesis of schizophrenia. <strong></strong></p><p><strong>Objective.</strong> To determine whether there were differences in breastfeeding patterns between patients with schizophrenia and controls. <strong></strong></p><p><strong>Method.</s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Individuals with schizophrenia are significantly less likely to have been breastfed than controls (67,68). The protective effect of breastfeeding may be due to breast milk being a rich source of DGLA, AA, EPA and DHA which may attenuate any adverse consequences of impaired fatty acid synthesis (10).…”
Section: Fatty Acid Intake and Neurodevelopmentmentioning
confidence: 99%
“…Individuals with schizophrenia are significantly less likely to have been breastfed than controls (67,68). The protective effect of breastfeeding may be due to breast milk being a rich source of DGLA, AA, EPA and DHA which may attenuate any adverse consequences of impaired fatty acid synthesis (10).…”
Section: Fatty Acid Intake and Neurodevelopmentmentioning
confidence: 99%
“…We noticed that, the odds of having SZ is reduced by 59% in breastfed individuals. There are various studies that have reported on the protective impacts of breastfed milk on SZ and potentially delayed onset of SZ symptoms 49 51 . Other studies have also reported that breastfeeding lowers the odds of developing other mental illnesses such as depression 28 and body dysmorphia 52 .…”
Section: Discussionmentioning
confidence: 99%